Static and seismic experiment for welded joints in modularized prefabricated steel structure. (September 2015) - Liu, X.C.; Xu, A.X.; Zhang, A.L.; Ni, Z.; Wang, H.X.; Wu, L.
Abstract: A beam–column joint used in a modularized prefabricated steel structure is proposed in this paper in which factory welding is completed. The model tests and finite element analysis for the static and seismic performance under monotonic static and cyclic loads were conducted on four full-size joints, the rules of static behaviour, hysteretic behaviour, skeleton curve, ductility performance, energy dissipation capacity, rotational capacity and stiffness dissipation were obtained. The effect of the chord and web thickness of the truss beam on the static performance and seismic capacity of the joint was studied, as well as the effect of the weld quality on the various performances of the joint. The simplified equations of the welded beam–column joint get along well with the experiment results. The study showed that weld quality significantly affects the failure mode and various mechanical performances of the welded joints; equal strength welds meet the static strength requirement, but it is difficult to meet the elastoplastic seismic requirements. The rotation stiffness of the joint is large, and the ultimate bearing capacity is high. The existence of an axillary plate at the end of the chord significantly improves the ductility performance, energy dissipation and plastic rotation capacity of the joint. A reduction of the chord and web thickness of the truss beam significantly reduces the ultimate bearing capacity of the joint, but it is not linearly proportional to the section area and does not significantly affect the ductility performance and the energy dissipation capacity. Graphical abstract: Highlights: A beam–column joint used in a modularized prefabricated steel structure is proposed. The static and seismic behaviour were obtained by model tests and finite element analysis. The simplified equations of the welded joint get along well with the test results. The rotation stiffness of the joint is large and the ultimate bearing capacity is high. The axillary plate of the chord significantly improves the seismic performance.